KINTAMANI’S COFFE SHOP CRAZE: PROFITS SOAR, NATURE PAYS THE PRICE - Haura, Haura (Jurnal Pacta Sunt Servanda, 2025)
The Kintamani area, Bali, is one of the leading tourist destinations with high ecological and cultural value. However, in recent years, the area has come under serious pressure due to the rampant construction of coffee shops that are carried out without adequate spatial planning and environmental supervision. This study aims to analyze the problem of weak regulation and supervision of the construction of coffee shops in the Kintamani conservation area, and how it impacts the environment and local culture. The method used is normative legal research, with a legislative approach and literature studies on primary and secondary legal sources, including Law Number 26 of 2007 concerning Spatial Planning, Law Number 32 of 2009 concerning Environmental Protection and Management, as well as regional regulations related to spatial planning and the environment. The results of the study show that weak regulatory implementation, lack of EIA evaluation, and absence of integrated supervision from local governments are the main causes of environmental degradation, conversion of agricultural land, and loss of local wisdom values. On the other hand, the lack of community participation in the licensing process exacerbates social inequality between investors and local residents. This study suggests the need for a reformulation of spatial policies based on the principles of sustainable development, consistent law enforcement, and strengthening institutional capacity in supervision. With better and sustainable management, the Kintamani area can maintain its ecological function and cultural value without sacrificing the economic potential of the tourism sector.